Role of Pharmacists in the Management of Patients with Obesity - Kovačević, Milena; Jovanović, Marija; Ćulafić, Milica (Archives of Pharmacy, 2024)
Obesity, a chronic disease, is increasingly prevalent worldwide, posing a significant public health challenge. It is often accompanied by comorbidities such as hypertension, cardiovascular disease, dyslipidemia, and diabetes, among others. Pharmacists play a vital role in managing obese patients, being readily accessible members of the healthcare team. Their responsibilities include initiating weight management services, conducting comprehensive patient interviews, devising personalized therapeutic plans, evaluating medications for potential weight gain, monitoring treatment effectiveness and safety, providing patient counseling, and making referrals to other healthcare professionals when necessary. Obesity induces notable changes in body composition that can impact the pharmacokinetic and pharmacodynamic properties of drugs, necessitating adjustments to dosing regimens. Lipophilic drugs typically experience a significant increase in volume distribution, while hydrophilic drugs may see only a moderate rise. The impact of obesity on drug elimination is relatively minor compared to its effects on distribution and varies depending on the specific metabolic or excretory pathway.
Keywords: obesity; pharmaceutical care; patient counselling; pharmacokinetics; drug dosing